Female genital cutting, women's health and development : the role of the World Bank - Rogo, K. O. (Khama O.); Subayi, Tshiya; Toubia, Nahid; World Bank (Washington, D.C. : World Bank, 2007)
This strategy paper provides a comprehensive understanding of the issue of female genital mutilation/cutting - scope, challenges, opportunities, best practices, and how communities, development agencies, and national governments can work together to eliminate the practices on the ground. The World Bank is committed to assisting governments in ending the practice of female genital cutting, as the practice has a direct, negative impact on the health and well-being of women around the world. The recommendations set forth in this paper take advantage of the World Bank's comparative advantage in dealing with governments. Continued silence perpetuates the practice, thereby undermining women's productivity.
Includes bibliographical references (p. 25-29)
Keywords: Circumcision; Female circumcision